The necessity and significance of linguocultural research of social media language - Elmatov , Shokir Nurmatovich (The Lingua Spectrum, 2026)
This article examines the linguocultural aspects of the language of social networks, which is an important part of modern digital communication space. The language units forming in social networks, discursive features, emotional-expressive means, as well as the integration of national and global culture are analyzed from the perspective of linguoculturology. The study substantiates the organic connection between the language of social networks and the mentality, cultural values, and worldview of society, while revealing the relevance and practical significance of scientifically studying this field.